A Modern perspective of Islamic Economics and Finance - Gündoğdu, Ahmet Şuayb (Emerald points, 2019)
This book aims to develop a blue print for Islamic economics and finance by starting at the grass roots of trade and commerce. It positions Islamic finance within the economic priorities of Islam while providing a cohesive understanding of Islamic economics and finance in a clear and practical manner